THEORETICAL ASPECTS OF INTERRELATION OF INNOVATIONS AND COMPETITIVENESS OF THE COUNTRIES IN INTERNATIONAL TRADE - V. Kirillov (Publishing House of the State University of Management, 2016)
In the modern innovative development of subjects of the world economy obvious unevenness of influence of innovations on line items of the certain countries in international trade is traced. In the article the main approaches to assessment of impact of innovations on competitive line items of the countries of the world in the international exchange are considered.